2011
DOI: 10.1016/j.jns.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of auditory brainstem function in lead-exposed children using stapedius muscle reflexes

Abstract: The purpose of this study was to investigate the neurological integrity and physiological status of the auditory brainstem tracts and nuclei in children with chronic lead (Pb) exposure using non-invasive acoustic stapedius reflex (ASR) measurements of afferent and efferent-neuromuscular auditory function. Following audiological examinations, uncrossed (ipsilateral) and crossed (contralateral) brainstem ASR responses were evoked by pure tone (500, 1000, and 2000 Hz), and broadband noise (bandwidth: 125-4000 Hz)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…However other studies found no association between concurrent blood lead and ABRs in older children [ 14 17 , 22 ]. Two studies of multi-age cohorts, ranging from toddlers to teenagers, without age-specific analyses, also found no association between concurrent blood lead and auditory function [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However other studies found no association between concurrent blood lead and ABRs in older children [ 14 17 , 22 ]. Two studies of multi-age cohorts, ranging from toddlers to teenagers, without age-specific analyses, also found no association between concurrent blood lead and auditory function [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the central dysfunction underlying their CAPD was rostral to the brainstem (Hall and Johnston, 2007). Abnormal AR findings, however, have been reported in a number of different central auditory disorders with established brain pathology, such as tumors of the brainstem (Jerger and Jerger, 1977), multiple sclerosis (Jerger et al 1986), head injury (Hall et al 1982), and more recently in lead poisoning (Counter et al 2011).…”
Section: Central Auditory Tests and Proceduresmentioning
confidence: 99%
“…Beyond ethanol, lead (Bini and Bollea, 1947), mercury (Oyanagi et al, 1989;Nagashima, 1997;Kern et al, 2012), and methyl bromide (Goulon et al, 1975) poisoning can result in a WKSlike pattern of brain damage particularly affecting inferior colliculi and visual and auditory functions (Otto and Fox, 1993;Counter et al, 2011).…”
Section: Other Diseases Involving the Inferior Colliculimentioning
confidence: 99%